OBSTACLES FACED BY STUDENTS IN SPEAKING ENGLISH LANGUAGE - Mohamed, Rashin Hasan. (IJRDO- Journal of Educational Research, 2022)
Speaking is regarded as an indicator of language proficiency in general. It is believed that a learner who can speak a particular language fluently is regarded as a proficient learner of that language. In Kingdom of Saudi Arabia, the English language is taken as a foreign language and taught from primary level to university level as a compulsory subject but Saudi students at schools and universities face many difficulties in speaking English fluently. Even after completing their graduate degree, some of them could not speak a little bit of English. This study tries to explore the difficulties faced by undergraduate level students and the possible causes of their difficulties in speaking skills. This is an empirical qualitative study in which the researcher adopted a questionnaire and semi-structured interview to collect data from 15 undergraduate level students studying at the Arts and Sciences College in Sharorah. The collected data were thermalized. This article analyzed the causes that make the students difficult to communicate in English and suggest some solutions that can overcome the difficulties. In this background, Descriptive nature of this present paper highlights the difficulties faced by college student in speaking English – a sociological reflection. Result revealed that student use English more frequent only inside the class and less frequent outside the class. Whereas, students‟ have limited time to learn English in class, and they still do not have enough encouragement to practice English outside the class in order to get familiar with English. Next, the Environment was the leading cause for the problems in learning English. Lack of reading habit and listening tends to challenge several problems in learning English. Recommendations in the light of findings are  also discussed in this article.